PRINCIPLES OF MULTIDISCIPLINARY MANAGEMENT IN PHYSICAL THERAPY - Kulaets, M. I.; Kulaets, V.M.; Kulaets, N.M.; Lapkovsky , E.Y.; Mykhaylyshyn, L.I. (The actual problems of regional economy development, 2020)
The article is devoted to the substantiation of the multidisciplinary management principles introduction in the processes of recovery and rehabilitation both for persons with disabilities and persons who are not formally established disability groups. The managerial aspect in ensuring an effective system of physical rehabilitation is defined as one of the measures to prevent the growth of the number of people with disabilities in society and an effective mechanism for restoring human life. It is proved that when organizing physical rehabilitation measures in domestic health care facilities it is advisable to follow the principles of world practice, which regulate the timeliness, quality, comprehensiveness, systematization of rehabilitation services, and physical therapy is given a prominent place in management processes to restore vital functions. As a result of the study, it is established that the Ukraine’s current rehabilitation practice lacks a comprehensive system of needs assessment, interdisciplinary work in providing services and their direct focus on the client, coordinated work of a multidisciplinary team and case management on a set of planning, organization, coordination, monitoring and evaluation services and resources for each individual, in order to choose the optimal rehabilitation strategy and tactics.